Orthopaedic Manifestations of Transverse Myelitis in Children. Issue 7 (August 2021) - Hariharan, Arun R.; Choi, Joseph H.; Cook, Ralph W.; Neal, Kevin M.; Rogers, Kenneth J.; Shrader, M. Wade; Ulusaloglu, Armagan C.; Howard, Jason J.
Abstract : Background: Transverse myelitis (TM) is a rare inflammatory disorder of the spinal cord. It can have a heterogeneous presentation with sensory, motor, and autonomic dysfunction. Neurological sequelae of TM include autonomic dysfunction, motor weakness, and/or spasticity. Studies describing orthopaedic deformities and treatments associated with TM are nonexistent. This purpose of this study was to describe the orthopaedic manifestations of TM in children. Methods: A multicenter retrospective review was conducted of patients, 0 to 21 years of age, with TM presenting over a 15-year period at 4 academic children's hospitals. Those with confirmed diagnosis of TM and referred to an orthopaedic surgeon were included. Demographics, orthopaedic manifestations, operative/nonoperative treatments, and complications were recorded. Descriptive statistics were used for data reporting. Results: Of 119 patients identified with TM, 37 saw an orthopaedic surgeon. By etiology, 23 were idiopathic (62%), 10 infectious (27%), 3 (8%) inflammatory/autoimmune, and 1 (3%) vascular. The mean age at diagnosis was 6.7 (SD: 5.5) years and at orthopaedic presentation was 8.4 (SD: 5.2) years. Orthopaedic manifestations included scoliosis in 13 (35%), gait abnormalities in 7 (19%), foot deformities in 7 (19%), upper extremity issues in 7 (19%), symptomatic spasticity in 6 (16%), lower extremity muscle contractures in 6 (16%), fractures in 6 (16%), hip displacement in 3 (8%), pain in 2 (5%), and limb length discrepancy in 2 (5%) patients. Seven children (19%) were seen for establishment of care. In all, 14 (38%) underwent operative intervention, mainly for soft-tissue and scoliosis management. Four patients had baclofen pump placement for spasticity management. Postoperative complications occurred in 36% of cases, most commonly because of infection. Neither topographic pattern nor location of lesion had a significant relationship with need for hip or spine surgery. Conclusions: This report describes the orthopaedic manifestations associated with TM in children, nearly 40% of whom required operative intervention(s). Understanding the breadth of musculoskeletal burden incurred in TM can help develop surveillance programs to identify and treat these deformities in a timely manner. Level of Evidence: Level IV Abstract : Supplemental Digital Content is available in the text.